BE_VERWALTUNGSGERICHT 100 2013 319 vom 28. April 2014 - BE Verwaltungsgericht (2014)
andere Schulung i.S. von Art. 18 VSG (Entscheid der Erziehungsdirektion des Kantons Bern vom 22. August 2013 - 4800.600.200.04/13 [628195]) | Bildung/Ausbildung